2012
DOI: 10.1007/s13277-012-0409-0
|View full text |Cite
|
Sign up to set email alerts
|

High RIN1 expression is associated with poor prognosis in patients with gastric adenocarcinoma

Abstract: The aim of this study was to investigate the expression and prognostic significance of RIN1 in gastric adenocarcinoma. RIN1 expression was analyzed using quantitative real-time PCR (qRT-PCR), Western blotting, and immunohistochemical staining on tissue samples from a consecutive series of 315 gastric adenocarcinoma patients who underwent tumor resections between 2003 and 2006. The relationship between RIN1 expression, clinicopathological factors, and patient survival was investigated. qRT-PCR results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…In so doing, we have uncovered novel functions for PRKCD and RIN1 that, although previously shown to function in receptor trafficking, had no known roles in regulating trafficking of soluble proteins. Of particular interest then is our finding that high expression of the PTPN14 substrates RIN1 and PRKCD correlated with poor patient survival in breast cancer, which concurs with previously published reports that PRKCD negatively correlates with survival in breast cancer patients (41) and RIN1 negatively correlates with survival in melanoma (42), gastric adenocarcinoma (43), bladder urothelial carcinoma (44), and non-small cell lung cancer (45). Recognizing that the trafficking of prometastatic factors and growth factor receptors is inhibited by PTPN14, and that it is promoted by PRKCD and RIN1, our findings reveal potential strategies for simultaneously reducing the mobilization of soluble factors and cell surface receptors that promote tumor cell growth and survival.…”
Section: Discussionsupporting
confidence: 90%
“…In so doing, we have uncovered novel functions for PRKCD and RIN1 that, although previously shown to function in receptor trafficking, had no known roles in regulating trafficking of soluble proteins. Of particular interest then is our finding that high expression of the PTPN14 substrates RIN1 and PRKCD correlated with poor patient survival in breast cancer, which concurs with previously published reports that PRKCD negatively correlates with survival in breast cancer patients (41) and RIN1 negatively correlates with survival in melanoma (42), gastric adenocarcinoma (43), bladder urothelial carcinoma (44), and non-small cell lung cancer (45). Recognizing that the trafficking of prometastatic factors and growth factor receptors is inhibited by PTPN14, and that it is promoted by PRKCD and RIN1, our findings reveal potential strategies for simultaneously reducing the mobilization of soluble factors and cell surface receptors that promote tumor cell growth and survival.…”
Section: Discussionsupporting
confidence: 90%
“…Although research studies have found that many aberrantly expressed genes in GC can contribute to the malignant behavior, the identification of novel molecular markers is still urgently needed 17,18. The WWC family protein has been implicated in human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…GGT6 has been linked to immune infiltration and inflammation and putatively to alterations in DNA methylation via changing levels of glutathione and methyl group availability [39,40]. Other CpGs are associated with genes related to immune function, including T cell regulation and inflammation, tumor initiation and angiogenesis (EBI3) [41,42], while other genes have been implicated in cancer aggressiveness (AQP9, RIN1) [43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%